An elastoplastic coupling mechanical model for hard and brittle marble with consideration of the first stress invariant effect. Issue 4 (3rd April 2018) - Yang, Fanjie; Zhou, Hui; Zhang, Chuanqing; Hu, Dawei; Lu, Jingjing; Meng, Fanzhen
Abstract : The mechanical properties of hard and brittle marble have three typical characteristics: (1) elastoplastic coupling, (2) strain hardening and softening and (3) shear dilatancy. To accurately describe the deformation and failure characteristics of marble, this paper developed an elastoplastic coupling mechanical model based on cyclic loading tests. The proposed mechanical model includes the following three characteristics. First, the elastic modulus was quantitatively related to both the first stress invariant and a specially defined internal variable. Second, evolution laws for strength parameters ( c and φ ) with the internal variable were suggested based on Mohr–Coulomb yield criterion. Third, an evolution law of the dilatancy angle that considered both the first stress invariant and the internal variable was proposed, and its identification method was provided. Then, the proposed mechanical model was embedded in FLAC 3D using C++ programming language. A triaxial compression experiment and an engineering case were simulated using the proposed model, respectively, and good agreements between the simulated results and test data were observed. Thus, the proposed model had a capability to accurately simulate the main mechanical characteristics of marble. Effort of this work could provide an important reference to accurately predict the mechanical response of rockmass in deep rock engineering.